IDENTIFIKASI PERMUKIMAN DI KAWASAN PESISIR UNTUK MENDUKUNG KEBIJAKAN DALAM PENGURANGAN RISIKO BENCANA DI PESISIR PANTAI SINE, KABUPATEN TULUNGAGUNG - Putranto, Anggoro; Jani, Jani (Social Landscape Journal, 2024)
The research was conducted in the coastal area of Sine Beach, Tulungagung Regency which is one of the coastal areas in the southern part of Java Island and has a high risk level of tsunami disaster. The purpose of this study, (1) to analyse the level of population settlement density, (2) to identify the type of population settlement. The method in this research uses a qualitative descriptive method. Data sources were obtained from secondary data and primary data, with data collection techniques analysing satellite images and field surveys. The results showed that (2) the level of settlement density in the coastal area of Sine Beach is the densest among coastal settlements in Tulungagung. While (2) the type of settlement is dominated by the settlement of fishermen with diverse settlement types, which are dominated by non-harvesting, semi-permanent and permanent settlements. Based on the level of settlement density and the type of settlement, the settlements in the coastal area of Sine Beach include the potential risk of exposure to coastal disasters such as high waves and Tsunami waves. So it is necessary to take action planning for coastal disaster risk reduction, such as disaster education, training, increasing public awareness in responding to disasters and minimising the risk of coastal disasters.